IMPLEMENTASI SIMRS DI RUMAH SAKIT UMUM MITRA DELIMA DALAM KESIAPAN PENERAPAN PERMENKES 24 TAHUN 2022 - Desi Syahbaniar (Health Care Media, 2023)
The flow of hospital services in the form of SIMRS at Mitra Delima General Hospital is quite running well and can serve patients every day with a large number of patients. Automatically without an officer operating SIMRS the patient's address often changes with the address of another patient. This study aims to determine the implementation of SIMRS (Khanza) at Mitra Delima General Hospital in readiness for the implementation of Permenkes 24 of 2022 concerning Medical Records. This type of research is descriptive qualitative using a descriptive qualitative approach. This research is about the readiness of SIMRS related to the implementation of Permenkes 24 of 2022 using the Human, Organization, Technology, and Net Benefit (Hot-Fit) Method. The results of this study found that the information system at RSU Mitra Delima uses SIM-RS Khanza and the readiness of the implementation of the hospital management system at RSU Mitra Delima by the Minister of Health Regulation No. 24 of 2022 has not been fully met. The conformity that has been fulfilled is only article 13 regarding the Activities of Implementing Electronic Medical Records which is still up to stage number (1), namely Patient Registration. The suggestion from this research is that a Special Team should be organized to manage, maintain and care for the Khanza application so that when there are obstacles it is immediately repaired and officers do not become double work.